You read best what you read most: An eye tracking study - Uroš Nedeljković; Kata Jovančić; Nace Pušnik (Journal of Eye Movement Research)
At the threshold of the digital era, Zuzana Licko was of the opinion that familiar letterforms owe legibility to centuries-long exposure and that all new, prototypically unmatching forms would be equally legible if used as frequently. This paper examined the legibility in the context of familiarity – is it affected by the time of exposure to a particular typeface or a typeface’s universal structure. We ran repeated measures tests with exposure period in-between. The experiment was conducted using for this purpose designed typefaces as stimuli, and the eye-tracking on-screen reading technology. The results confirmed that one’s familiarity with a typeface influences one’s reading speed. The universal letter structure, recognised by Frutiger as the prototype skeleton, is the constant that a priori provides legibility. On the other hand, the period of exposure to uncommon letterforms also has a positive impact on legibility. Therefore, considering that the period of familiarity with the humanist letterforms has been continuous since their establishment, the maxim from the dawn of the digital era can be regarded as valid.